Compostos bioativos em produtos lácteos adicionados de polpa de açaí e Camu-camu suplementados com bactérias probióticas - Campos, Daniela Cavalcante dos Santos (2017)
The acai (Euterpe oleracea Mart.) and camu-camu (Myrciaria dubia (Kunth) McVaugh) are native fruits of the Amazon that have excellent bioactive properties related to phenolic compounds, anthocyanins and vitamin C. Fermented dairy products are considered excellent food matrices sources of nutrients, which can be supplemented with fruits, fibers and a variety of probiotic microorganisms to increase the nutritional and functional power of these products. In this sense, the objective of this work was to produce dairy products fermented with açaí and camu-camu and supplemented with strains of Bifidobacterium (BB-12) and Lactobacillus acidophilus (LA-5), as well as to evaluate the effect of these microorganisms on the behavior of the bioactive components and antioxidant activity of the fermented products during 28 days of storage. Açaí fruits were obtained in a private orchard (Boa Vista-RR), and camu-camu in a population located on the banks of the Urubu River (Boa Vista-RR). For the preparation of fermented milk (LF) and yogurt (IO), 8% of sugar, 4% of skimmed milk powder, probiotic cultures (LF) and traditional lactic (IO) cultures were added to UHT milk. coagulation for 4 hours to pH of 4.8. The pulps and fermented products were evaluated as pH, titratable acidity, soluble solids, moisture, total solids, proteins, lipids, ashes, reducing and total sugars, total and defatted dry extract and calorific value. The instrumental color was determined only on the products fermented with açaí, by reading the parameters L *, a * and b * using the CIELAB color scale, on days 0 and 28 of evaluation. The BB-12 and LA-5 counts were performed on the products fermented with açaí and camucamu, obeying the specificities of each microorganism. The quantification of total phenolics, anthocyanins and antioxidant activity in both pulps and fermented products were performed following official methodologies and preliminary tests. Both counts of microorganisms and determination of bioactive components were performed on day 0 and every 7 days during the period of 28 days. For the sensorial analysis of the fermented milks were applied sorting and acceptability tests using hedonic scale. The açaí pulp complied with the Brazilian legislation regarding the physico-chemical and nutritional characteristics, while the camu-camu agreed with data from the literature. The fermented milks met the current legislation regarding the physical-chemical and nutritional characteristics. As regards the effects of post-acidification on fermented milks and yoghurts, it was verified that they were more evident between days 0 and 7 of evaluation, being higher in the yogurts with camu-camu (IC) and açaí (IA), due to the presence of L. bulgaricus. The colorimetric analysis showed discolorations in the yoghurts and milks fermented with açaí as a function of anthocyanin degradation. Fermented milks with açaí (LFA) and camu-camu (LFC) were classified as probiotics according to the Brazilian legislation showing a count above 6 Log CFU g-1, except LFC with 20% of pulp. The phenolic compounds, anthocyanins and antioxidant activity in fermented milks and yoghurts increased their contents with the increase in pulp percentage, and reduced at the end of storage. The antioxidant activity showed excellent correlation with phenolic and anthocyanin contents. The sensorial analysis showed that the fermented milks showed good acceptability by the tasters.